Safety of bioinductive bovine collagen implants for arthroscopic rotator cuff repair - Hideki Kinjo, MD; Naoki Suenaga, MD, PhD; Naomi Oizumi, MD, PhD; Kotaro Nishida, MD, PhD (JSES International, 2025)
Background: Bioinductive reconstituted type I bovine collagen implants for augmenting arthroscopic rotator cuff repair (ARCR) may improve the healing rate and thickness of repaired tendons. However, there are concerns regarding the inflammatory responses and foreign body reactions associated with the use of foreign substances. This study aimed to evaluate the safety of type I bovine collagen bioinductive implants in ARCR. Methods: A retrospective cohort study was conducted on 74 patients who underwent ARCR using the surface-holding method; 37 patients were treated with bioinductive collagen implants (R group) and 37 patients were treated without implants (N-R group). The participants underwent routine preoperative blood tests at 1 and 2 weeks postoperatively. Magnetic resonance imaging (MRI) was performed at 1 week and 6-8 weeks postoperatively. The safety of the implant was assessed using serum inflammatory responses, such as C-reactive protein (CRP) and white blood cell (WBC) counts, and the presence of effusions in the glenohumeral joints and subacromial bursa on MRI. In addition, the need for reoperation owing to infection or foreign body reactions was examined. Statistical analyses were performed using Mann–Whitney U tests and Wilcoxon signed–rank tests for CRP and WBC counts and Fisher’s exact probability tests for effusions on MRI. Statistical significance was set at P < .05. Results: CRP levels and WBC counts normalized within 2 weeks postoperatively in both the R and N-R groups, with no significant differences between the groups at any time point. Effusions in the glenohumeral joints and subacromial bursa were present in both groups and were not significantly different between the R and N-R groups at 1 and 6-8 weeks postoperatively. No reoperations due to infection or inflammatory responses were observed within 6 months postoperatively in either group. Conclusion: The use of reconstituted type I bovine collagen bioinductive implants in ARCR did not significantly affect postoperative inflammatory responses or increase the risk of effusion. The absence of reoperations due to clinical infections or foreign body reactions further supports the safety of the implants.